The Bewick’s Swans at Slimbridge - Scott, Peter (Wildfowl, 1966)
The study of individual birds in the wild has been made possible by capture and marking techniques followed by further catching or by close observation, as well as the normal flow of information through recoveries. Observation of breeding birds has been the easiest because of their strong attachment to a limited area. Some work has been done outside the breeding season using conspicuous marks in the form of harness or collar attachments. Individual variation in birds of one species has been recognised for many years but it has been exploited for research purposes only in a limited wayfor instance in observing family behaviour in the White-fronted Goose, and in the recording of occurrences of the Lesser White-fronted Goose, at Slimbridge, both concerned mainly with the variation in the black belly bars, and in differences in the shape and extent of the white frontal shield.